2014
DOI: 10.5171/2014.547185
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Evaluate the Role of Different Variables in Results of TIPU for Hypospadias

Abstract: The objective of this article is to evaluate the role of different variables affecting the results of tubularised incised plate repair for hypospadias.We prospectively evaluated 125 patients of TIPU repair from April 2009 to October 2011. Study parameters were age, severity of hypospadias, degree of curvature and torsion, size of penis and glans, width of urethral plate, development of spongiosum and complication rate. Patients were classified into five groups by age; Group I-6 months to 2 years, Group II-2 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Some authors used it to identify a < 8 mm narrow urethral plate (Holland & Smith, 2000; Nguyen, Snodgraas, & Zaontz, 2004). However, according to the more recent classification (Bhat, Bhat, et al, 2014; Bhat, Sabharwal, et al, 2014), it has been reported that it is unreasonable to define a fix value for each patient, instead the native urethral diameter should be referenced to determine the width of the urethral plate. Though debates about the optimum urethral plate width continue, as the urethral plate diameter increases, post‐operative complications are known to reduce.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors used it to identify a < 8 mm narrow urethral plate (Holland & Smith, 2000; Nguyen, Snodgraas, & Zaontz, 2004). However, according to the more recent classification (Bhat, Bhat, et al, 2014; Bhat, Sabharwal, et al, 2014), it has been reported that it is unreasonable to define a fix value for each patient, instead the native urethral diameter should be referenced to determine the width of the urethral plate. Though debates about the optimum urethral plate width continue, as the urethral plate diameter increases, post‐operative complications are known to reduce.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that complications can increase with age when comparing early childhood with late childhood. 28 29 UP dimensions vary as age increases, and considerable changes develop in the UP structure. Older UPs consist more of collagen content, fewer cells, and elastic tissue and are depleted of vascular sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the spongiosum and width of the urethral plate were graded intraoperatively as per published literature into poorly, moderately and well developed. [11] Similarly, the width of urethral plate is assessed and categorized into wide, when it can be tubularized easily without incision (on the largest acceptable size catheter in normal proximal urethra). If urethral plate requires a superficial incision for tubularization; then, it is considered to be an average one, and when it requires a deep incision then urethral plate is considered as narrow.…”
Section: Methodsmentioning
confidence: 99%